ANALISIS STRATEGI PERENCANAAN SUMBER DAYA MANUSIA DALAM MENINGKATKAN EFEKTIVITAS PENANGANAN BENCANA DI KANTOR BADAN PENANGGULANGAN BENCANA DAERAH KOTA GUNUNGSITOLI - Restina Waruwu; Palindungan Lahagu; Syah Abadi Mendrofa; Odaligoziduhu Halawa (Jurnal Publikasi Manajemen Informatika, 2025)
This study aims to analyze the human resource (HR) planning strategy in improving the effectiveness of disaster management at the Regional Disaster Management Agency (BPBD) of Gunungsitoli City. The research employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that the HR planning strategy implemented by BPBD Gunungsitoli City has been carried out fairly well. This is reflected in the high quality of employee performance, the ability of personnel to work independently, continuous improvement of skills through training and development programs, and effective coordination and communication among work units. In addition, the establishment of the Rapid Response Team (TRC), the implementation of disaster simulation exercises, and cross-sector collaboration have contributed to enhancing the effectiveness of disaster management. However, several challenges remain, including a shortage of personnel, unequal distribution of training opportunities among employees, and limitations in supporting facilities and infrastructure. Therefore, strengthening HR planning through the recruitment of competent personnel, continuous capacity-building programs, and the optimization of coordination and evaluation systems is necessary to further improve the effectiveness of disaster management at BPBD Gunungsitoli City.